2018
DOI: 10.1038/s41380-018-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Control of non-homeostatic feeding in sated mice using associative learning of contextual food cues

Abstract: Feeding is a complex motivated behavior controlled by a distributed neural network that processes sensory information to generate adaptive behavioral responses. Accordingly, studies using appetitive Pavlovian conditioning confirm that environmental cues that are associated with food availability can induce feeding even in satiated subjects. However, in mice, appetitive conditioning generally requires intensive training and thus can impede molecular studies that often require large numbers of animals. To addres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…More recent work identified a connection between the BLA and the INS as critical for mediating hunger-dependent enhancement of food cue responses. This supports a model whereby the interactions between the BLA and INS can gate appetitive action selection in response to food cues by weighing the predicted interoceptive outcome value with the context of current physiological needs (545,(595)(596)(597)(598).…”
Section: Pavlovian Conditioning: Stimulus-induced Eatingsupporting
confidence: 72%
“…More recent work identified a connection between the BLA and the INS as critical for mediating hunger-dependent enhancement of food cue responses. This supports a model whereby the interactions between the BLA and INS can gate appetitive action selection in response to food cues by weighing the predicted interoceptive outcome value with the context of current physiological needs (545,(595)(596)(597)(598).…”
Section: Pavlovian Conditioning: Stimulus-induced Eatingsupporting
confidence: 72%
“…Further examination of these studies revealed that two focused on punishment rather than negative reinforcement (Beattie and Corr 2010 ; Wimmer et al 2018 ) and two examined positive rather than negative reinforcement (Amsel et al 1971 ; Marx 1969 ). One study reported that spaced training was more effective than massed training with negative reinforcement in mice (Stern et al 2020 ). Finally, one study included horses (McCall et al 1993 ) trained on an avoidance (Pavlovian) conditioning task.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex (insula) mediates top-down modulation of feeding and drinking behaviors in response to taste quality (1, 2), homeostatic/visceral states (3,4), innate threat (3), and learned stimuli (5)(6)(7)(8)(9)(10), as well as the modulation of emotional (11) and social (3,12,13) behaviors. In particular, the modulation of feeding or drinking is differentially regulated by distinct regions of the insula along the anterior-posterior (A-P) axis (1), and region-specific projections to the amygdala complex are suggested to underlie the behavioral control.…”
Section: Introductionmentioning
confidence: 99%